Perlindungan Hukum Irregular Migrant Workers Indonesia Dalam Prespektif Hak Asasi Manusia - Nur Efsari, Hana (UI Scholars Hub, 2023)
The increase in migrant workers is also accompanied by an increase in various violations of the human rights of migrant workers. Problems of human rights violations are becoming more serious for Irregular Migrant Workers, hence the need for appropriate measures to ensure the protection of their human rights. As an international entity, states are burdened with full rights and responsibilities in protecting, upholding and fulfilling the human rights of precarious migrant workers. Although in Law no. 18 of 2017 concerning the Protection of Migrant Workers does not accommodate non-permanent migrant workers, but they are still individuals whose rights are protected by the 1945 Constitution. Apart from that, protection in the international arena is carried out by ratifying the Human Rights Protection Convention. All Migrant Workers and Their Families and the International Covenant on Civil and Political Rights, therefore the state must protect the rights of migrant workers as stated in this convention. Governments at the regional level provide protection through the ASEAN Consensus on the Protection and Promotion of Migrant Workers' Rights, although it is only morally binding. Unfortunately, various human rights violations still occur among Indonesian non-permanent migrant workers, including, there are still Indonesian migrant workers in Malaysia whose personal documents are taken by their employers or human agents. East Nusa Tenggara Province (NTT) is an area sending TKI which has the highest number of cases. biggest trade. A number of migrant workers from NTT died in Malaysia and within a short time, a female migrant worker from Indonesia was reported to have died. In addition, Indonesian migrant workers receive the death penalty abroad